The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1183/13993003.00869-2018
|View full text |Cite
|
Sign up to set email alerts
|

Predicting outcomes in rheumatoid arthritis related interstitial lung disease

Abstract: The aim of this study was to compare radiology-based prediction models in rheumatoid arthritis-related interstitial lung disease (RAILD) to identify patients with a progressive fibrosis phenotype.RAILD patients had computed tomography (CT) scans scored visually and using CALIPER and forced vital capacity (FVC) measurements. Outcomes were evaluated using three techniques, as follows. 1) Scleroderma system evaluating visual interstitial lung disease extent and FVC values; 2) Fleischner Society idiopathic pulmona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(105 citation statements)
references
References 22 publications
4
99
0
2
Order By: Relevance
“…Previous studies have reported UIP as the predominant radiological pattern and predictor of mortality [14,42]; however, recent studies report a UIP proportion of 40%-54% [40,47]. A recent study showed that radiology-based prediction models in RA-ILD can identify patients with a progressive fibrosis phenotype [112], and that the visual extent of ILD in combination with FVC values, as previously seen in scleroderma [113], predicts outcome in RA-ILD. Morisset et al [47] showed that the addition of HRCT patterns to the ILD-GAP prediction model did not improve its performance.…”
Section: Prognosismentioning
confidence: 97%
“…Previous studies have reported UIP as the predominant radiological pattern and predictor of mortality [14,42]; however, recent studies report a UIP proportion of 40%-54% [40,47]. A recent study showed that radiology-based prediction models in RA-ILD can identify patients with a progressive fibrosis phenotype [112], and that the visual extent of ILD in combination with FVC values, as previously seen in scleroderma [113], predicts outcome in RA-ILD. Morisset et al [47] showed that the addition of HRCT patterns to the ILD-GAP prediction model did not improve its performance.…”
Section: Prognosismentioning
confidence: 97%
“…Most RA-ILD patients with UIP have a similar slightly improved prognosis compared with IPF, with acute exacerbations having a major impact on survival [57,[65][66][67][68]. Conversely, recently published data suggest the existence of a subset of RA-ILD patients with UIP in whom the disease stabilises in the long term, differentiating these patients from those with IPF [69].…”
Section: Ctd-ildmentioning
confidence: 99%
“…In IPF, it is controversial whether having honeycomb is a poor prognostic factor [11,15]. However, recent reports indicated that the development of honeycombing in RA-ILD was a poorer prognostic factor than CT pattern (e.g., UIP, NSIP) [9,11]. Similarly, our recent study also showed having honeycomb to be a poor prognostic factor in RA-ILD [10].…”
Section: Discussionmentioning
confidence: 48%
“…However, an unclassifiable pattern on HRCT is present to some extent in the RA-ILD population because RA-ILD exhibits a diversity of patterns [6,8]. Recent reports including our study showed that the major HRCT pattern in RA-ILD was mixed nonspecific interstitial pneumonia (NSIP) and UIP [9,10]. However, radiological honeycomb pattern is a poorer prognostic factor than a UIP pattern on HRCT [10].…”
Section: Introductionmentioning
confidence: 57%